Revealing the drivers of parasite community assembly: using avian haemosporidians to model global dynamics of parasite species turnover - de Angeli Dutra, Daniela (2023)
Why do some regions share more or fewer species than others? Community assembly relies on the ability of individuals to disperse, colonize and thrive in new regions. Therefore, many distinct factors, such as geographic distance and environmental features, can determine the odds of a species colonizing a new environment. For parasites, host community composition (i.e. resources) also plays a key role in their ability to colonize a new environment as they rely on their hosts to complete their life cycle. Thus, variation in host community composition and environmental conditions should determine parasite turnover among regions. Here, we explored the global drivers of parasite turnover using avian malaria and malaria-like (haemosporidian) parasites. We compiled global databases on avian haemosporidian lineages distributions, environmental conditions, avian species distributions and functional traits, and ran generalized dissimilarity models to uncover the main drivers of parasite turnover. We demonstrated that haemosporidian parasite turnover is mainly driven by geographic distance followed by host functional traits, environmental conditions and host distributions. The main host functional traits associated with high parasite turnover were the predominance of resident (i.e. non-migratory) species and strong territoriality, while the most important climatic drivers of haemosporidian turnover were mean temperature and temperature seasonality. Overall, we established the importance of geographic distance as a key predictor of ecological dissimilarity and showed that host resources influence parasite turnover more strongly than environmental conditions. We also evidenced that parasite turnover is most pronounced among tropical and less interconnected regions (i.e. regions with mostly territorial and non-migratory hosts). Our findings provide a robust foundation for the prediction of avian pathogen spread and the emergence of infectious diseases.